Evolutionary-based image encryption using RNA codons truth table - Mahmud, Maqsood; Atta-ur-Rahman; Lee, Malrey; Choi, Jae-Young (Optics and laser technology, 2020)
•The ribonucleic acid (RNA) concepts and genetic algorithm (GA) are used for high secure image encryption.•GA employs logistic map and RNA to generate its initial population.•The proposed method has high resistance against common attacks in the field. Symmetric image cryptography is a mechanism in which image pixels are encrypted into some meaningless format called cipher image. Only authorized users have access to the secret code for symmetric key encryption. In this paper a new symmetric image encryption method has been proposed using the concepts of ribonucleic acid (RNA) sequence and genetic algorithm (GA), called RNA-GA. The proposed method starts by generating specified number of initial cipher images using logistic map function. Then, the initial cipher images are converted to the corresponding one-dimensional binary sequences and relevant codons array using codons truth table. The codons array are then updated using encryption key and encryption RNA tables to form the initial population of genetic algorithm. Next, genetic algorithm optimizes the population using selection, crossover, and mutation operators. The results approve high resistance of the proposed method against well-known attacks and entropy of 7.9987 regarding standard image of size 256×256 after 30 repetitions.